Specifika komunikace v diskusích na internetu - Junková, Bohumila (Stylistyka, 2019)
Discussions on the Internet show the changes of traditional conception of language styles. Even though the texts are undoubtedly written down they are spontaneous and colloquial Czech is primarily used there. High occurrence of spoken colloquial language can be understood as an attempt to establish a contact with other discussion participants.The dichotomy of speech and writing is disappearing. Slight differences between written and spoken texts are not observed only in everyday communication style of the Internet discussions and that is why traditional distinguishing of speech and writing is not always possible.